Numerical modelling of penstock flow in dam - Zahari N.M.; Zawawi M.H.; Aziz N.A.; Nurhikmah F.; Abas A.; Ng F.C.; Sidek L.M.; Radzi M.R.M. (American Institute of Physics Inc., 2024)
This paper presents the numerical modeling on the flow in dam penstock structure using conventional finite volume method (FVM) simulation software, ANSYS Fluent. The water flows in the bottom outlet section that comprised of four penstocks were successfully simulated. The numerical model was validated with an experiment, which a considerably low discrepancy of 12%. It was found that the middle section of each penstock observed the highest flow velocity, indicating the regions sustained large stress from the rapid flow, which gives the higher deformation. However, the flow dynamics across all four penstocks are similar. Overall, this numerical study showed that the application of the FVM simulation tool to visualize the penstock flow is viable and useful for the subsequent dam reliability analysis. 2023 AIP Publishing LLC.